Searching for new physics using optically levitated sensors - Moore, David C; Geraci, Andrew A (Quantum science and technology, 2021)
We describe a variety of searches for new physics beyond the standard model of particle physics which may be enabled in the coming years by the use of optically levitated masses in high vacuum. Such systems are expected to reach force and acceleration sensitivities approaching (and possibly eventually exceeding) the standard quantum limit over the next decade. For new forces or phenomena that couple to mass, high precision sensing using objects with masses in the fg-ng range have significant discovery potential for new physics. Such applications include tests of fundamental force laws, searches for non-neutrality of matter, high-frequency gravitational wave detectors, dark matter searches, and tests of quantum foundations using massive objects.